2016
DOI: 10.1107/s2053229616000577
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin: a citrus flavonoid displaying potent physiological activity

Abstract: Nobiletin [systematic name: 2-(3,4-dimethoxyphenyl)-5,6,7,8-tetramethoxy-4H-chromen-4-one; C21H22O8] is a flavonoid found in citrus peels, and has been reported to show a wide range of physiological properties, including anti-inflammatory, anticancer and antidementia activities. We have solved the crystal structure of nobiletin, which revealed that the chromene and arene rings of its flavone moiety, as well as the two methoxy groups bound to its arene ring, were coplanar. In contrast, the C atoms of the four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
(20 reference statements)
3
8
0
Order By: Relevance
“…This result indicated that NOB interacted with CAGE by hydrogen bondings 40,41 ; that is, the H atom of the hydroxyl group in CAGE (6.1–6.5 ppm in NMR spectra) acts as a hydrogen bonding donor, and the O atoms of the carbonyl and methoxy groups in NOB might act as multipoint hydrogen bonding acceptors. These results appear to be in good agreement with the NOB crystal structure 42 . Therefore, it is possible that the hydrogen bondings between NOB and CAGE contributed to the improvement in the solubility of NOB.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This result indicated that NOB interacted with CAGE by hydrogen bondings 40,41 ; that is, the H atom of the hydroxyl group in CAGE (6.1–6.5 ppm in NMR spectra) acts as a hydrogen bonding donor, and the O atoms of the carbonyl and methoxy groups in NOB might act as multipoint hydrogen bonding acceptors. These results appear to be in good agreement with the NOB crystal structure 42 . Therefore, it is possible that the hydrogen bondings between NOB and CAGE contributed to the improvement in the solubility of NOB.…”
Section: Resultssupporting
confidence: 88%
“…NMR analysis indicated that the H atom of the hydroxyl group in CAGE was a hydrogen bonding donor and the two O atoms in the skeleton of the flavonoid, or all seven methoxy groups in NOB, appeared to be hydrogen bonding acceptors. This result was supported by the results of X ray crystal structural analysis 42 . Generally, the skeletal structures of flavonoids hinder their dissolution in water through strong π-π interactions.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, 50 µM nobiletin supplementation in IVM upregulated the expression of CYP51A1 in blastocysts. This is in line with the results of nobiletin supplementation in liver cell culture (HepG2), showing upregulation of CYP1 (Cytochrome P450s family) and improved cholesterol synthesis due to full methoxylation in the A-ring of nobiletin chemical structure [10,51]. Hence, nobiletin could act differently depending on the cell type, probably due to the bioactivity or its chemical structure, which causes that CYP51A1 might be down or upregulated to control cholesterol availability, however, more in deep studies are necessary to corroborate this information.…”
Section: Discussionsupporting
confidence: 87%
“…The biological activities of nobiletin depend on its chemical structure; nobiletin is absorbed easily due to its lipophilic nature and high permeability. An X-ray crystal structure study revealed that the chromene and arene rings and the bound methoxy groups create a chiral molecule that can adopt a variety of conformations 34 . This molecular flexibility may support a wide range of physiological activities by binding the different target receptors of specific signaling pathways.…”
Section: Discussionmentioning
confidence: 99%